Comprehensive multiphase NMR applied to a living organism. Issue 8 (25th April 2016) - Mobarhan, Yalda Liaghati; Fortier-McGill, Blythe; Soong, Ronald; Maas, Werner E.; Fey, Michael; Monette, Martine; Stronks, Henry J.; Schmidt, Sebastian; Heumann, Hermann; Norwood, Warren; Simpson, André J.
Abstract : Comprehensive Multiphase NMR provides an overview as to all components (liquids, gels, solids) in a living organism. Abstract : Comprehensive multiphase (CMP) NMR is a novel technology that integrates all the hardware from solution-, gel- and solid-state into a single NMR probe, permitting all phases to be studied in intact samples. Here comprehensive multiphase (CMP) NMR is used to study all components in a living organism for the first time. This work describes 4 new scientific accomplishments summarized as: (1) CMP-NMR is applied to a living animal, (2) an effective method to deliver oxygen to the organisms is described which permits longer studies essential for in-depth NMR analysis in general, (3) a range of spectral editing approaches are applied to fully differentiate the various phases solutions (metabolites) through to solids (shell) (4) 13 C isotopic labelling and multidimensional NMR are combined to provide detailed assignment of metabolites and structural components in vivo . While not explicitly studied here the multiphase capabilities of the technique offer future possibilities to study kinetic transfer between phases ( e.g. nutrient assimilation, contaminant sequestration), molecular binding at interfaces ( e.g. drug or contaminant binding) and bonding across and between phases ( e.g. muscle to bone) in vivo . Future work will need to focus on decreasing the spinning speed to reduce organism stress during analysis.